1993
DOI: 10.3354/dao015187
|View full text |Cite
|
Sign up to set email alerts
|

A genetic probe for identification of the turbot aquareovirus in infected cell cultures

Abstract: A nucleic acid hybridization assay has been developed that can detect small amounts of the turbot aquareovirus (TRV) in infected cells. Complementary DNAs were synthesized from the dsRNA genome segments of TRV and used to generate a large number of recombinant plasmids. Plasrnids corresponding to genomic segments 1 through 8 were identified by Northern blot analysis. A randomly selected clone, Clone 66, hybridizing to genome Segment 8, showed high specificity hybridizing only RNA from TRV, and not with the RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The VP7 protein, encoded by genome segment 10, has been shown to be glycosylated and is the major outer capsid protein (Samal et al, 1990 ;Subramanian et al, 1994 ;Shaw et al, 1996). In addition, using reciprocal RNA-RNA hybridization studies, it has been shown that genome segment 10 is the most variable gene between genogroups A and B (Lupiani et al, 1993 a). The nucleotide sequences of the major outer capsid proteins of other members of the family Reoviridae have been reported (Both et al, 1982 ;Purdy et al, 1985 ;Bassel-Duby et al, 1985 ;Chen et al, 1990 ;Qian et al, 1991).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The VP7 protein, encoded by genome segment 10, has been shown to be glycosylated and is the major outer capsid protein (Samal et al, 1990 ;Subramanian et al, 1994 ;Shaw et al, 1996). In addition, using reciprocal RNA-RNA hybridization studies, it has been shown that genome segment 10 is the most variable gene between genogroups A and B (Lupiani et al, 1993 a). The nucleotide sequences of the major outer capsid proteins of other members of the family Reoviridae have been reported (Both et al, 1982 ;Purdy et al, 1985 ;Bassel-Duby et al, 1985 ;Chen et al, 1990 ;Qian et al, 1991).…”
mentioning
confidence: 99%
“…Like rotaviruses, aquareoviruses have a genome composed of 11 segments of doublestranded RNA (dsRNA ; Lupiani et al, 1995). On the basis of cross-hybridization studies using total genomic RNA probes, aquareoviruses have been classified into five genogroups (A-E ; Lupiani et al, 1993 a). Among these, genogroup A was found to be the most prevalent.…”
mentioning
confidence: 99%
See 3 more Smart Citations